ANALISIS PERSEPSI GENERASI Z TERHADAP KUALITAS LAYANAN TRANSPORTASI ONLINE DI KOTA TASIKMALAYA - Ila Nursa’adah; Novia Nissya Prawesty; Dea Fuji Lestari (Transpublika Publisher, 2022)
This study aims to determine how Generation Z's perception of online transportation quality services in the city of Tasikmalaya is. Qualitative descriptive research methods are used to explain this phenomenon. In collecting data, the researcher conducted a survey in the form of a questionnaire distributed via google form. The research sample was 50 respondents using online transportation, with a simple random sample technique or random sampling. The indicators used to see the perception of Generation Z on the quality of online transportation services are the people factor, physical factors, and application factors. The collected data is then processed and interpreted in depth to get a conclusion. The results of the study describe that generation Z’s perception of online transportation is seen from the perception of people factors (drivers), physical factors (facilities) and application factors, namely generation Z mostly agree that drivers have a friendly attitude, agile, punctual, uphold safety in driving. as well as an expert in driving a vehicle. Then the physical factors or the vehicles/facilities provided can also be concluded as good and supportive in supporting the transportation process. Furthermore, the application factor is also easy to understand, detailed information about the price to the trip being booked, and the mapping of features in the application is also very good.